Comparison of Novel Biochars and Steam Activated Carbon from Mixed Conifer Mill Residues - Nathaniel Anderson; Hongmei Gu; Richard Bergman (Energies, 2021)
There is increasing demand in environmental remediation and other sectors for specialized sorbents made from renewable materials rather than hard coals and minerals. The proliferation of new pyrolysis technologies to produce bio-based energy, fuels, chemicals, and bioproducts from biomass has left significant gaps in our understanding of how the various carbonaceous materials produced by these systems respond to processes intended to improve their adsorption properties and commercial value. This study used conventional steam activation in an industrial rotary calciner to produce activated carbon (AC) from softwood biochars made by three novel pyrolysis systems. Steam was injected across four heating zones ranging from 816 °C to 927 °C during paired trials conducted at calciner retention times of 45 min and 60 min. The surface area of the three biochars increased from 2.0, 177.3, and 289.1 m2 g−1 to 868.4, 1092.9, and 744.8 m2 g−1, respectively. AC iodine number ranged from 951 to 1218 mg g−1, comparing favorably to commercial AC produced from bituminous coal and coconut shell. The results of this study can be used to operationalize steam activation as a post-processing treatment for biochar and to expand markets for biochar as a precursor in the manufacture of specialized industrial sorbents.